Perancangan Sistem Informasi Penyewaan Lapangan Futsal Di Wilayah Cipondoh Berbasis Web - Rahmat Jaya; Irpan Kusyadi (CV. Multi Kreasi Media, 2022)
Information systems have also begun to enter the field of sports, as a medium of information that provides information such as futsal field rentals. The Cipondoh area has several futsal field rental places as a supporting facility for futsal players who want to exercise. Because for now, even for players who want to rent a futsal field, especially in the Cipondoh area, they are having difficulty getting information about a futsal field rental place and players still need to come directly to the location to find out the condition of the futsal field. With the current website-based information system, it will be easier for futsal players who want to rent a field using a website-based system. By using the website-based information system, players who rent the futsal field can make bookings, the available futsal field schedule, field conditions, field rental times and payment transactions. As for the design of this system using the waterfall method using programming languages such as PHP, MySQL. Notepad++. And all the descriptions in the design of this system using UML modeling such as use case diagrams, activity diagrams, sequence diagrams, to class diagrams.